The Effectiveness Of Celery And Rosella Flower Decoctions In Reducing High Blood Pressure At The Elderly Integrated Health Post (Posyandu) In Rw 01, Kebon Baru Village, South Jakarta In 2025 - Nafa Andini (CV. AFDIFAL MAJU BERKAH, 2026)
Hypertension in the elderly is vulnerable due to vascular degeneration, with a high prevalence in Indonesia (34.1%) and side effects of pharmacological drugs encourage complementary herbal therapy. This study aims to compare the effectiveness of celery and rosella decoction in reducing MAP in hypertensive elderly at Posyandu Lansia RW 01, South Jakarta. The type of research is a quantitative quasi-experimental two-group pretest-posttest; population 60 hypertensive elderly, sample 40 (purposive, 20/group). Instruments: Omron sphygmomanometer, observation sheet; analysis Paired/Independent t-test (Jamovi, α=0.05). The results showed a decrease in MAP celery 8.90 mmHg (p<0.001) vs rosella 4.45 mmHg (p<0.001), a significant difference (p<0.001). Celery decoction is more effective as a community complementary therapy.